Xenoantibody response to porcine islet cell transplantation using GTKO, CD55, CD59, and fucosyltransferase multiple transgenic donors. (20th March 2014) - Chen, Yan; Stewart, John M.; Gunthart, Mirja; Hawthorne, Wayne J.; Salvaris, Evelyn J.; O'Connell, Philip J.; Nottle, Mark B.; d'Apice, Anthony J. F.; Cowan, Peter J.; Kearns‐Jonker, Mary
Abstract Background Promising developments in porcine islet xenotransplantation could resolve the donor pancreas shortage for patients with type 1 diabetes. Using α1, 3‐galactosyltransferase gene knockout (GTKO) donor pigs with multiple transgenes should extend xenoislet survival via reducing complement activation, thrombus formation, and the requirement for exogenous immune suppression. Studying the xenoantibody response to GTKO/hCD55/hCD59/hHT islets in the pig‐to‐baboon model, and comparing it with previously analyzed responses, would allow the development of inhibitory reagents capable of targeting conserved idiotypic regions. Methods We generated IgM heavy and light chain gene libraries from 10 untreated baboons and three baboons at 28 days following transplantation of GTKO/hCD55/hCD59/hHT pig neonatal islet cell clusters with immunosuppression. Flow cytometry was used to confirm the induction of a xenoantibody response. IgM germline gene usage was compared pre‐ and post‐transplant. Homology modeling was used to compare the structure of xenoantibodies elicited after transplantation of GTKO/hCD55/hCD59/hHT pig islets with those induced by GTKO and wild‐type pig endothelial cells without further genetic modification. Results IgM xenoantibodies that bind to GTKO pig cells and wild‐type pig cells were induced after transplantation. These anti‐non‐Gal antibodies were encoded by the IGHV3‐66*02 (Δ28%) and IGKV1‐12*02 (Δ25%) alleles, for the immunoglobulin heavy and light chains, respectively. IGHV3‐66 is 86.7% similar to IGHV3‐21 which was elicited by rhesus monkeys in response to GTKO endothelial cells. Heavy chain genes most similar to IGHV3‐66 were found to utilize the IGHJ4 gene in 85% of V‐D regions analyzed. However, unlike the wild‐type response, a consensus complementary determining region 3 was not identified. Conclusions Additional genetic modifications in transgenic GTKO pigs do not substantially modify the structure of the restricted group of anti‐non‐Gal xenoantibodies that mediate induced xenoantibody responses with or without immunosuppression. The use of this information to develop new therapeutic agents to target this restricted response will likely be beneficial for long‐term islet cell survival and for developing targeted immunosuppressive regimens with less toxicity.